2001
DOI: 10.1542/peds.108.1.e6
|View full text |Cite
|
Sign up to set email alerts
|

Thiazide Diuretics Arrest the Progression of Nephrocalcinosis in Children With X-Linked Hypophosphatemia

Abstract: ABSTRACT. Objective. X-linked hypophosphatemia (XLH) is characterized clinically by rickets, hypophosphatemia, and hyperphosphaturia. Conventional treatment of XLH with oral phosphate and vitamin D is associated with increased urinary calcium excretion and nephrocalcinosis. Thiazide diuretics decrease urinary calcium excretion. The objective of this study was to determine the effect of thiazide diuretics on the clinical and radiologic course of nephrocalcinosis in children with XLH.Methods. The effect of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In a small number of children with XLH treated with phosphate and calcitriol, the addition of thiazide/ amiloride presumably provided protection against the development of NC [23]. Seikaly and Baum [24] showed that the addition of thiazides arrested the progression of NC in their XLH patients; however, no resolution of NC was observed (personal communication). We are not aware of any previous study showing ultrasonographic resolution of nephrocalcinosis in patients with XLH spontaneously or after treatment with anticalciuric diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…In a small number of children with XLH treated with phosphate and calcitriol, the addition of thiazide/ amiloride presumably provided protection against the development of NC [23]. Seikaly and Baum [24] showed that the addition of thiazides arrested the progression of NC in their XLH patients; however, no resolution of NC was observed (personal communication). We are not aware of any previous study showing ultrasonographic resolution of nephrocalcinosis in patients with XLH spontaneously or after treatment with anticalciuric diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive doses, e.g., more than 50 ng/kg per day of 1,25(OH) 2 D 3 , should not be used long term [53,54]. For treatment of hypercalciuria, thiazides might be considered [55].…”
Section: Abnormal Regulation Of Pth In Hypophosphatemic Rickets?mentioning
confidence: 99%
“…Commonly, infants younger than six months present with hypocalcemic tetany or seizures, whereas older children present with failure to thrive or skeletal deformiti es 9 . Vitamin D-dependent rickets, type I results from abnormaliti es in the gene coding for 25 10,11 . Hypophosphatemic vitamin D-resistant rickets or X linked hypophosphataemia (XLH) is a hereditary disease manifesti ng marked hypophosphataemia caused by renal tubular loss of phosphate into urine and an associated decrease in the calcium and potassium ion product.…”
Section: Types Of Ricketsmentioning
confidence: 99%
“…The systemic fi ndings of XLH include bowed legs because of a body load showing immature skeletal bone calcifi cati on, spinal curvature deformiti es and beading of the ribs called rachiti c rosary [25][26][27] . Other causes of rickets include renal disease, medicati ons, and malabsorpti on syndromes (Table 1 8, [9][10][11][12][13][14][15] ).…”
Section: Types Of Ricketsmentioning
confidence: 99%
See 1 more Smart Citation